Consumer Perception Towards Social Media Advertisements : A Study Done in a Semi-Urban City of South India - Padival, Adesh; Michael, Lidwin Kenneth; Hebbar, Sunith (Indian Journal of Marketing, 2019)
The drastic growth in the usage of social media among the people in India has created a new platform for promotion, that is, social media advertisements. However, the effectiveness of these advertisements has been interrogated by many. Lower acceptance of advertisements has been one of the major challenges faced by the marketers. Henceforth, it is vital to understand the critical factors influencing the consumers' attitude towards social media advertisements. This study thus identified and analyzed the factors influencing behavioral intention of the consumers concerning social media advertisements. The constructs like corporate reputation, emotional appeal, informativeness, creativity, irritation, and materialism were considered to affect the attitude, which in turn influenced the behavioral intention of consumers. The study was carried out in a semi-urban city of Karnataka, South India and the data were collected from 217 respondents. The analysis was carried out using the partial least square approach. The results indicated that the two factors - creativity and informativeness had a significant influence on the attitude of the consumers towards social media advertisements. The study further analyzed the moderating role of the factor - 'gender' between the identified constructs and attitude. The results revealed the existence of differences among the male and female respondents towards the advertisements. Further, based on these outcomes, appropriate practical implications of the findings were discussed. Subsequently, this study will certainly help in gaining better insights into the consumers' perception towards social media advertisements and will assist the marketers in framing effective advertisement strategies.